PROGRAM PENGEMBANGAN KEWIRAUSAHAAN (PPK) DI UNIVERSITAS SARJANAWIYATA TAMANSISWA - Sri Hermuningsih; Retno Widiastuti; V. Reza Bayu Kurniawan (LPPM IST AKPRIND Yogyakarta, 2018)
Program Pengembangan Kewirausahaan (PPK)/Entrepreneurship Development Program is a program delivered by the Directorate of Research and Community Service (DRPM) to the universities in Indonesia in order to encourage student entrepreneurs through integrated program and method developed by universities. University of Sarjanawiyata Tamansiswa (UST) as one of the private universities focusing on the development of Micro Small and Medium Entreprises (MSME) continues to provide guidance to students to establish and develop small-medium scale business. The objectives of this program is encourage science and technology based student entrepreneurs through an integrated program involving researchers, lecturers, practitioners, and external campus’ business incubator. This program activities include tenant recruitment and establishment of business groups, management training and business skills for tenants, stimulant funding, mentoring of production processes, and marketing. The implementation of this program in 2017 was participated by 102 students from Department of Industrial Engineering, Department of Agribusiness, Department of Management, and Department of Art Education in University of Sarjanawiyata Tamansiswa and divided into 21 teams. Eleven selected tenant groups have been intensively supervised in UST business incubator.